HEALTH INEQUALITY AND ECONOMIC GROWTH IN NIGERIA - Ogu, Callistus (African Journal of Social and Behavioural Sciences, 2023)
This study examined the impact of health inequality on Nigeria's economic growth from 1990 to 2021. the call to close the gap in health inequality in developing countries, especially Nigeria has become inevitable to encourage economic growth and development in the country. This study made use of Autoregressive Distributed Lag in ascertaining the short and long-run relationship between the components of health inequality and economic growth in Nigeria. the variables used are; Gross Domestic Growth Rate, as the dependent variable and also a proxy for economic growth, life expectancy at birth, infant mortality, maternal mortality, and health expenditure formed the independent variables. In any case from the findings, it was identified that only life expectancy at birth was positively significant to economic growth in Nigeria while the reverse was the case in the other three independent variables. It was concluded that budget allocation on health should be improved upon to close the gap in health inequality in Nigeria.